Socio-demographic and Economic Factors Associated with Adherence to Anti-Tuberculosis Treatment - Hossain, Md Motahar; Flora, Meerjady Sabrina; Md Shahidullah, -; Amin, Md Nurul; Mosharref, Murshida; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Tuberculosis is one of the most significant health problems in Bangladesh. Adherence to TB treatment is crucial to achieving cure while avoiding the emergenceofdrug resistance. Non-adherence to anti-tuberculosis treatment may result in persistent infectiousness and a higher rate of treatment failure, relapse and drug resistance and therefore, it’sa significant barrier to the success in tuberculosis control. Objectives: To determine the socio-demographic and economic factors influencing adherence to anti-tuberculosis treatment among tuberculosis patients. Materials and Methods: This case control study was carried out among purposively selected 47 cases and 94 controls in selected DOTS centres of Dhaka city from January 2010 to July 2010. Data were collected by face to face interview using a semi-structured questionnaire. Results: Males were 2.5 times more likely to be non-adherent and among them day-labourer and main earning member were more commonly non-adherent (p<0.05). Low per capita income and irregularity of monthly income were significantly (p<0.01) associated with non-adherence. Conclusion: Non-adherence is associated with the risk factors that are modifiable by the correction of socio-demographic and economic characteristics as a whole. So the highest priority in fighting against non-adherence therefore must be to reduce poverty for its prevention especially targeting the patients of low economic status. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 39-41